Perspectives on Open Science and The Future of Scholarly Communication: Internet Trackers and Algorithmic Persuasion - Ignat, Tiberius; Ayris, Paul; Gini, Beatrice; Stepankova, Olga; Özdemir, Deniz; Bal, Damla; Deyanova, Yordanka (Frontiers in Research Metrics and Analytics, 2021)
The current digital content industry is heavily oriented towards building platforms that track their users’ behaviour and seek to convince them to stay longer and come back sooner onto the platform. In parallel to this, the authors are incentivised to publish more and to become champions of dissemination. Arguably, these incentive systems are built around public reputation and are supported by a system of metrics, hard to be assessed. Generally, the digital content industry is permeable to non-human contributors (algorithms that are able to generate content and reactions), anonymity and identity fraud. It is pertinent to study if early signs of track and persuasion are currently present in scholarly communication. This perspective paper presents a pilot study that aims to determine the opportunity for conducting research about the use of “track and persuade” technologies in scholarly communication. We collected observations on a sample of 150 websites that are relevant to the scholarly communication landscape. Through this work, we tried to identify a) what the essential questions are, b) how much the readers, authors and reviewers are tracked when they interact with such websites, c) what good practices are recommended for future research in this area, and d) whether citizen science is a suitable approach to further research in this field. The findings could contribute to determining a broader solution for building trust and infrastructure in scholarly communication. The principles of Open Science will be used as a framework to see if they offer insights into this work going forward.